Lead and cadmium removal in synthetic wastewater using constructed wetland - Mohd Shahrel, Baharudin (2008)
Heavy or toxic metals are harmful to humans and other organism even in small quantities. This research focused on the removal efficiency of the heavy metals (lead and cadmium) using constructed wetland system. Constructed wetlands are the low cost engineered systems that have been designed and constructed to utilize the natural processes involving wetland vegetation, soils, and the associated microbial assemblages to assist in treating wastewaters. In addition, constructed wetland treatment had demonstrated the good capacity in treating the wide range of wastewaters including the hazardous industrial waste. In this research, the free water surface constructed wetland was conducted in the batch mode system and loaded with Pistia stratiotes (water lettuce) in order to study the removal efficiency of cadmium and lead elements. From the study, it was found that the Pistia stratiotes is an aquatic plant that growing rapidly and also a high biomass crop with an extensive root system that can enhance the heavy metals removal. There were two parameters studied in this research which were varying in number of plant, and varying pH conditions. The removal of lead and cadmium in the constructed wetland were increased when the numbers of plant increased. The constructed wetland containing 15-plants recorded the highest removal with 99.28% for lead removal and 65.89% for cadmium removal. For the pH condition experiment, the neutral condition (pH = 7) showed the better removal compared to the base and acidic conditions. As a conclusion, constructed wetland system with wetland plant (Pistia stratiotes) showed good removal efficiency for lead and cadmium from the industrial wastewater.